Respuesta :
Note that –4|–2x + 6| = –24 can be greatly simplified by dividing both sides by -4: |-2x+6| = 6. This, in turn, can be simplified by dividing everything by 2:
|-x+3| = 3. There are two solutions:
Case 1: -x+3 is already positive. The absolute value operator is unneeded. -x+3 = 3. Then x = 0.
Case 2: -x+3 is negative. Then rewrite |-x+3| = 3 as -(-x+3) = 3. Solving for x: x - 3 = 3, and x = 6.
The solution set is {0, 6}.
The correct answers are the x = 6 and x = 0.
In order to find this, we can follow the order of operations.
–4|–2x + 6| = –24
Divide by -4
|–2x + 6| = 6
Since it is now equal to a absolute value, we have to solve for the positive and negative versions of the final answer. Let's start with the positive.
-2x + 6 = 6
-2x = 0
x = 0
Now for the negative
-2x - 6 = -6
-2x = -12
x = 6
These would be your two answers.